2014
DOI: 10.1039/c4ta01324g
|View full text |Cite
|
Sign up to set email alerts
|

rGO/nano Sb composite: a high performance anode material for Na+ion batteries and evidence for the formation of nanoribbons from the nano rGO sheet during galvanostatic cycling

Abstract: The rGO/Sb nanocomposite formation of nanoribbons from the rGO nanosheets is responsible for high capacity and capacity retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 38 publications
0
80
0
2
Order By: Relevance
“…Generally, the highfrequency semicircle and the semicircle in the mediumfrequency region are attributed to the SEI layer and/or contact resistance, and the charge-transfer impedance on the electrodeelectrolyte interface, respectively. [37][38][39] The linear portion is designated to Warburg impedance which is attributed to the diffusion of sodium ion into the bulk of the electrode materials. [37][38][39] According to the modied Randles equivalent circuit shown in the inset of Fig.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the highfrequency semicircle and the semicircle in the mediumfrequency region are attributed to the SEI layer and/or contact resistance, and the charge-transfer impedance on the electrodeelectrolyte interface, respectively. [37][38][39] The linear portion is designated to Warburg impedance which is attributed to the diffusion of sodium ion into the bulk of the electrode materials. [37][38][39] According to the modied Randles equivalent circuit shown in the inset of Fig.…”
Section: +mentioning
confidence: 99%
“…[37][38][39] The linear portion is designated to Warburg impedance which is attributed to the diffusion of sodium ion into the bulk of the electrode materials. [37][38][39] According to the modied Randles equivalent circuit shown in the inset of Fig. 7, the charge-transfer resistance (R ct ) of N-TiO 2 (B) electrode is 185.1 U, which is much lower than those of TiO 2 powder electrode (708.7 U) and TiO 2 (B) electrode (456.3 U).…”
Section: +mentioning
confidence: 99%
“…In order to utilize the high energy storage capabilities of alloy anodes and achieve stable cycling performance, the sizes of active materials need to be made as small as possible to allow the electrode to buffer the large stress from volume change in the repeated alloying/de-alloying process. Many research groups have demonstrated that antimony based composite anode materials can deliver high capacity for sodium storage as well as stable cycle performance through alloy-based reaction in sodium-ion batteries [12][13][14]. Electrospun Nitrogen-doped carbon fibers, CNT enhanced lithium titanate-carbon fibers composite and antimony-carbon fibers composite were also investigated as freestanding high performance anode materials for sodium-ion batteries [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning and electrospray methods have been widely used in the synthesis of functional materials on polymer fabricated networks of a freestanding nature, which can provide flexibility for the convenience of electrode fabrication [19][20][21][22]. Graphene is a frequently used agent in the synthesis of composite electrode materials for sodium-ion batteries [14,[23][24][25][26]. The strategy of introducing graphene into composite creates a simple and effective path to enhance the electrochemical performance of electrode materials, since the graphene is highly conductive and it is an electrochemical active anode material for sodium-ion batteries [27].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the deteriorations of Sb anode, modification strategies including nanosizing strategy, [153] hollow structure design, [154] Sb-based alloy/intermetallic design (including Ag 3 Sb, [155] AlSb, [156,157] Mg 3 Sb 2 , [158] Sn-Sb, [159] Cu 2 Sb, [160][161][162][163] Mo 3 Sb 7 , [164] NiSb, [165] ), Sb/C composite design (including Sb/C nanofiber, [166] Sb/C microsphere, [167] Sb/C nanosheet, [168] Sb/graphene, [169][170][171] Sb/3D carbon network [172] ), have been developed. Sb nanocrystalls with mean size of 10-20 nm and narrow size distributions of 7-11% were reported as anode materials in LIBs and SIBs by He et al [153] As compared to microstructured Sb, Sb anodes with 10 and 20 nm in diameter exhibited enhanced cycling stability and rate capability, indicating the positive effect of nanosizing strategy for Sb-based anode materials.…”
Section: Antimony Based Anode Materialsmentioning
confidence: 99%